2013
DOI: 10.1002/zoo.21071
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of zoo visitors' exhibit experiences and reactions

Abstract: Visiting a zoo or aquarium is not only fun, but can also have a positive impact on visitors' knowledge and attitudes regarding animals and the environment. The biggest challenge, however, is for these institutions to strategically provide opportunities for cognitive and affective learning while simultaneously facilitating enjoyment and fun. Recent studies in zoos and aquaria have examined various factors that can influence learning such as engaging visitors' emotions or connecting with visitors' prior knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…A number of zoo studies have investigated the factors associated with visitor experience and satisfaction. Luebke and Matiasek (2013) found that viewing animals is highly correlated to visitor satisfaction as well as their cognitive and affective reactions. The study, therefore, suggests that zoos need to focus on animal visibility and animal behavior in the planning and management of exhibits.…”
Section: Introductionmentioning
confidence: 96%
“…A number of zoo studies have investigated the factors associated with visitor experience and satisfaction. Luebke and Matiasek (2013) found that viewing animals is highly correlated to visitor satisfaction as well as their cognitive and affective reactions. The study, therefore, suggests that zoos need to focus on animal visibility and animal behavior in the planning and management of exhibits.…”
Section: Introductionmentioning
confidence: 96%
“…The opportunity to view an animal in close contact appears to elicit an emotional response and to allow people to strengthen a felt relationship or connection to animals (Bodamer and Sankovic 2000;Clayton et al 2009Clayton et al , 2014Luebke and Matiasek 2013). Kellert (1996) has reported that zoo visitors show more humanistic attitudes (that is, similar to attitudes towards humans) toward nonhuman animals than do nonvisitors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Luebke and Matiasek (2013) found that visitors reported that "visiting [zoos] has made me more concerned about the wellbeing of wildlife" and "The exhibit made wildlife conservation issues more meaningful to me" (means above 5 on a 7-point scale) (see also Falk et al 2007). Clayton et al (2014) reported that zoo visitors scored higher on concern about climate change compared to the general U.S. public, and Powell and Bullock (2014) found that emotional response to the animals was positively correlated with support for environmental conservation.…”
Section: Introductionmentioning
confidence: 99%
“…A "profound experience", or moment of personal connection with wildlife can engender significant positive attitudes towards a species and its conservation (Weiler and Ham, 2011). Accordingly, zoos seek to design exhibits which allow visitors a good view of animals at close proximity, and which create an impression of the animal's natural environment (Fernandez et al, 2009;Luebke and Matiasek, 2013). In addition to the exhibits themselves, zoos provide a range of interpretive materials and experiences which aim to reveal to visitors the significance of the animals on exhibit (Moscardo et al, 2004).…”
Section: Interactive Technology At the Zoomentioning
confidence: 98%